A Phase I, Randomized, Double-Blind, Placebo-Controlled Clinical Trial to Evaluate the Safety and Tolerance of Oil Palm Phenolics (OPP) in Healthy Volunteers - Muhammad Ismail Tadj, Nur Balqis; Ibrahim, Nurul ‘Izzah; Haji Mohd Saad, Qodriyah; Tg Abu Bakar Sidik, Tg Mohd Ikhwan; Leow, Soon-Sen; Fairus, Syed; Naina Mohamed, Isa (Frontiers in Pharmacology, 2022)
Background & aim: Oil palm phenolics (OPP) is an oil palm aqueous-by-product that is rich with phenolic contents and pre-clinical research has shown that OPP has a great potential to be further develop as an anti-hyperlipidemic agent. Hence, in order to introduce OPP into market, its safety profile need to be established by undergoing clinical trial phase 1 on healthy humans. Methods: A parallel, placebo-controlled, randomized, double-blinded clinical trial was conducted for two months on 100 healthy subjects aged 20-40 years old. This trial was registered at clinicaltrials.gov (NCT04164446). The subjects were randomly allocated to four treatment arms with 25 participants each: placebo, 250mg OPP, 1000mg OPP and 1500mg OPP. During the trial, subjects were required to consume four capsules simultaneously per day. Withdrawal of fasting blood for hematology, liver and renal function analysis and medical examination were conducted at baseline (day 1), day 30 and day 60. For monitoring, vital signs (blood pressure and pulse rate) as well as weight measurement were taken during each visit. Results: Minor adverse events (AE) were reported in all groups especially at high dose (1500mg) but none were serious adverse event (SAE). Fasting blood parameters between control and all OPP-treated groups demonstrated no statistically significant difference from baseline to day 60. Conclusion: With no major AE and SAE reported and no abnormal findings in biochemistry and hematology results, OPP supplementation in capsule form is safe to be taken up to 1500mg a day.